Two Brothers with Bardet-Biedl Syndrome Presenting with Chronic Renal Failure - Cem Sahin; Bulent Huddam; Gulhan Akbaba; Hasan Tunca; Emine Koca; Mustafa Levent (Case Reports in Nephrology)
Bardet-Biedl Syndrome (BBS) is a rarely seen autosomal recessive transfer disease characterised by retinal dystrophy, obesity, extremity deformities, mental retardation, and renal and genital system anomalies. BBS shows heterogenic transfer. To date, 18 genes (BBS1–18) and 7 BBS proteins have been defined as related to BBS. All of the defined BBS genes have been shown to be related to the biogenesis or function of cilia. Renal failure accompanying the syndrome, especially in the advanced stages, is the most common cause of mortality. Therefore, as one of the major diagnostic criteria, renal damage is of great importance in early diagnosis. This paper presents the cases of two brothers with BBS who presented with chronic renal failure.